2004
DOI: 10.1074/jbc.m402305200
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 Expression Confers Resistance to Apoptosis in Breast Cancer MCF-7 Cells by a Mechanism of NF-κB-dependent XIAP Up-Regulation

Abstract: The aggressiveness of a tumor is partly attributed to its resistance to chemotherapeutic agent-induced apoptosis. Cysteine-rich 61 (Cyr61), from the CCN gene family, is a secreted and matrix-associated protein, which is involved in many cellular activities such as growth and differentiation. Here we established a cell model system to examine whether stable expression of Cyr61 in MCF-7 cells can confer resistance to apoptosis and identify possible participating mechanisms. We showed that stable cell lines overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
155
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 82 publications
13
155
1
Order By: Relevance
“…The fact that, in certain circumstances, NF-kB can regulate the expression of the IAPs in a differential manner has recently been demonstrated by others. It has been shown in this regard that connective tissue growth factor Cyr61 triggers activation of NF-kB and subsequent NF-kB-induced upregulation of XIAP but not of cIAP2 in breast carcinoma cells (Lin et al, 2004). Of note, detachment-dependent upregulation of XIAP occurred in each cell line tested in this study.…”
Section: Discussionsupporting
confidence: 47%
“…The fact that, in certain circumstances, NF-kB can regulate the expression of the IAPs in a differential manner has recently been demonstrated by others. It has been shown in this regard that connective tissue growth factor Cyr61 triggers activation of NF-kB and subsequent NF-kB-induced upregulation of XIAP but not of cIAP2 in breast carcinoma cells (Lin et al, 2004). Of note, detachment-dependent upregulation of XIAP occurred in each cell line tested in this study.…”
Section: Discussionsupporting
confidence: 47%
“…Microtubule cytoskeleton dysfunction has been shown to activate NF-kB (Rosette and Karin, 1995; Das and Mechanisms of IL-6 upregulation by paclitaxel T-H Wang et al White, 1997). Most recent reports have suggested activation of NF-kB to be an antiapoptotic mechanism of cancer cells (Dong et al, 2002;Uzzo et al, 2002;Dey et al, 2003;Flynn et al, 2003;Lin et al, 2004), although contrary observations have also been reported (Huang and Fan, 2002). Notably, NF-kB is also an important downstream transcription factor in the TLR4-MyD88 signaling cascade (Takeda et al, 2003) ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…The current results regarding the role of CYR61 in gemcitabine resistance provide a rationale for inhibiting CYR61 or both CTGF and CYR61 in combination with gemcitabine (and nab-paclitaxel) in PDAC patients. Although our study is the first to identify a role for CYR61 in nucleoside transporter expression and gemcitabine resistance, CYR61 has recently been implicated in therapy resistance in the contexts of several other cancers, including renal cell carcinoma (39), breast cancer (58,59), acute myeloid leukemia (60) and ovarian cancer (61), which indicates that CYR61 may be a promising target to improve efficacy of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%